Multiple sclerosis prevalence and risk factors among the Altai Region population - I. V. Smagina; Yu. N. Ignatova; S. A. Yelchaninova; A. S. Fedyanin (Бюллетень сибирской медицины)
In Altai Region, Russian Federation, multiple sclerosis (MS) prevalence is found in 39,9 cases of 100000 with wide variation in certain areas of the territory and ethnic corridor widening. Genotypes HLA-DRBI (13/15, 15/15, 15/3, 3/other) are associated with MS risk factors; recent illnesses (before 15 years old), such as chickenpox, rubella, herpes, chronic tonsillitis, and also head trauma before the illness debut are not associated with MS hazard.